Open Heritage : Community-Driven Adaptive Reuse in Europe: Best Practice - Mieg, Harald A. (2023)
"Open Heritage" is a response to the urgent need for a more open definition of cultural heritage, of the parties involved in protecting and maintaining it, and of the relevant planning processes in order to ensure the sustainable reuse of cultural heritage in times of climate change, social inequality and social plurality.